PERAN ORIENTASI PELANGGAN DEPARTEMEN SALES DAN MARKETING DALAM MENINGKATKAN PENDAPATAN DI PETIT BOUTIQUE HOTEL SOLO - Bartolomeus Herawan Mintardjo (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2022)
The purpose of this study was to determine the role of customer orientation carried out by the sales and marketing department to increase revenue at Petit Boutique Hotel Solo, using qualitative descriptive research methods with data collection techniques through observation and interviews. The result of this research is that the orientation role applied by the sales and marketing department has succeeded in increasing revenue for Petit Boutique Hotel Solo. In addition to customer orientation that is applied to increase revenue, the sales and marketing department of Petit Boutique Hotel Solo uses a sales funnel to see customer prospects which will later become potential new markets that can help increase revenue at Petit Boutique Hotel Solo.